2023
DOI: 10.1088/1361-648x/acb4d1
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-scale controlled growth of MoS2 by magnetron sputtering: from in-plane to inter-connected vertically-aligned flakes

Abstract: Recently, Molybdenum disulfide (MoS2) has attracted great attention due to its unique characteristics and potential applications in various fields. The advancements in the field have substantially improved at the laboratory scale however, a synthesis approach that produces large area growth of MoS2 on a wafer scale is the key requirement for the realization of commercial two-dimensional technology. Herein, we report tunable MoS2 growth with varied morphologies via RF sputtering by controlling growth parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Explore new materials and large-area growth: We must continue to study new thermal and photoelectric materials, such as two-dimensional materials, topological insulators, organic-inorganic hybrid materials, and perovskites, which are expected to cover a wider range of wavelength bands and improve the performance and sensitivity of broadband photodetectors. To produce cost-effective FPAs ultimately, research into large-area deposition techniques for materials is also necessary, including various scalable deposition techniques such as magnetron sputtering [111], pulsed-laser deposition [112], atomic layer deposition [113], van der Waals growth [114], and others.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Explore new materials and large-area growth: We must continue to study new thermal and photoelectric materials, such as two-dimensional materials, topological insulators, organic-inorganic hybrid materials, and perovskites, which are expected to cover a wider range of wavelength bands and improve the performance and sensitivity of broadband photodetectors. To produce cost-effective FPAs ultimately, research into large-area deposition techniques for materials is also necessary, including various scalable deposition techniques such as magnetron sputtering [111], pulsed-laser deposition [112], atomic layer deposition [113], van der Waals growth [114], and others.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Raman spectroscopy, a powerful nondestructive characterization tool, has been used to study different morphologies of MoS 2 [23,24]. It is frequently reported that four firstorder Raman active modes at 32 cm −1 (E 2g…”
Section: Effect Of the Height Between The Si Substrate And The Mo Sou...mentioning
confidence: 99%
“…Sensor response, selectivity, resolution, accuracy, and precision limits of sensing devices are constantly being increased. 2,7,8 Their use and application potential are also quickly growing at the same time. In this study, we make a selective acetone sensor based on 2D/2D heterostructure of WO 3 /WS 2 to work in biomedical-to industrial-scale applications with the capability of continuous exhaled breath monitoring verified by experimental and computational studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that sensors that can deliver accurate timely information have a crucial role to play in limiting the transmission of viruses and diseases, thereby saving many lives, particularly during this period of sanitary emergency known as COVID-19. , Researchers in this field are continuously seeking more sensitive and precise detection techniques, measurement principles, and innovative analytical methodologies to develop modern sensing devices and instruments. , However, the majority of volatile organic compound (VOC) sensors on the market today provide data on total VOCs rather than individual VOC, and no sensor is available to work for biomedical-scale (lower concentrations) to industrial-scale (higher concentrations) applications, while selectivity is another issue that sensor technology faces. , Due to social expectations, critical sensor performance characteristics including sensitivity, selectivity, stability, and utility must be increased. Sensor response, selectivity, resolution, accuracy, and precision limits of sensing devices are constantly being increased. ,, Their use and application potential are also quickly growing at the same time. In this study, we make a selective acetone sensor based on 2D/2D heterostructure of WO 3 /WS 2 to work in biomedical- to industrial-scale applications with the capability of continuous exhaled breath monitoring verified by experimental and computational studies.…”
Section: Introductionmentioning
confidence: 99%